General calculation method of power boundary of multiport power electronic transformer - Li, Junchi; Wu, Junyong; Xiong, Fei (Frontiers in Energy Research, 2024)
In the multiport power electronic transformer (MPET), cascaded H-bridge (CHB) converters are adopted to form the medium voltage AC port. Multiple low voltage DC ports can be constructed by paralleling the output terminals of dual active bridge converters into multiple clusters. The distributed generation and the DC load of multiple low voltage DC ports will be distributed in three phases, evenly or unevenly. When the power of low voltage DC ports is uneven, power imbalance problem will arise. The front-end cascaded H-bridge converters in the low voltage DC ports with high power generation or load power will face the risk of over modulation. In this article, a general calculation method (GCM) of power boundary of MPET is proposed. The reference power of each low voltage DC port can be adjusted according to the power boundary to avoiding over modulation. The GCM of power boundary can be applied to the situation where multiple ports have multiple power flow directions simultaneously. The effectiveness of the GCM of power boundary is verified by DC port power boundary simulation results of two four ports IDBS-MPETs.